Motivation in foreign language learning. Gamification, Personal Learning Environments and higher education. Design of a pedagogical proposal - Dany Andrey Latorre Méndez (University of Las Tunas, 2024)
The article "Motivation in Foreign Language Learning: Gamification, Personal Learning Environments and Higher Education" presents an innovative pedagogical proposal integrating gamification and Personal Learning Environments (PLEs) to improve students' motivation and academic performance in higher education. The paper details how gamification, by incorporating elements and techniques of video games in the educational environment, encourages active participation and increases student motivation. In parallel, PLEs allow students to personalize their educational process, adapting it to their interests and capabilities, which promotes autonomy and responsibility. The proposal is structured in several stages, from skills diagnosis to implementing and evaluating the pedagogical strategy, using practical tools such as the gamification platform Gimkit and motivation surveys such as "The Instructional Materials Motivation Survey" (IMMS). The expected results include increased motivation, academic performance, and the development of self-directed and personal learning management skills. This practical approach ensures that the proposed strategy can be easily implemented and its effectiveness can be measured. This approach seeks to respond to the need for innovation in teaching methods and aligns with the demands of an increasingly digitized and student-centered educational environment. Combining gamification and PLEs is a powerful strategy to enhance the learning process, making it more engaging, interactive, and tailored to each learner's needs.